Effect of environmental tobacco smoke on COX‐2 and SHP‐2 expression in a periodontitis rat model. (3rd September 2020) - Li, Xiangjun; Liang, Xiangyang; Li, Shujuan; Qi, Xia; Du, Ning; Yang, Dongru
Abstract: Objectives: To investigate the effects of environmental tobacco smoke (ETS) on the inflammatory process of periodontitis by evaluating bone loss and the expression of cyclooxygenase‐2 (COX‐2) and Src homology phosphotyrosine phosphatase 2 (SHP‐2). Materials and Methods: Eighty 6‐month‐old male SD rats were randomized into four groups (10 rats/group/per time point): (a) normal group, (b) ETS group, (c) ligature‐induced periodontitis group, and (d) ligature‐induced periodontitis + ETS group. After treatment with ligature and/or ETS for 8 and 12 weeks, the levels of alveolar bone resorption and the expressions of COX‐2 and SHP‐2 in periodontal tissue were analyzed using histology and immunohistochemistry. Results: The ligature‐induced periodontitis group displayed increased bone resorption and elevated expression of COX‐2 and SHP‐2 in periodontal tissues compared to the normal and ETS groups at 8 and 12 weeks. Furthermore, bone resorption and COX‐2 and SHP‐2 levels in the ligature‐induced periodontitis + ETS group were significantly increased compared to those in the normal and ligature‐induced periodontitis groups at both 8 and 12 weeks. Conclusion: Environmental tobacco smoke increased alveolar bone loss in periodontitis with enhanced expression of COX‐2 and SHP‐2 in periodontal tissues. Further investigation is needed to explore the role of COX‐2 and SHP‐2 in ETS‐associated periodontitis.